2017
DOI: 10.1002/pen.24730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mold opening on the properties of PLA samples obtained by foam injection molding

Abstract: Foam injection molding is a process by which complex, thick parts with a cellular core and a compact solid skin can be manufactured. The addition of a physical blowing agent under high pressure allows the decrease of the viscosity and the glass transition temperature of the gas/polymer melt. These features of the foam injection molding are very beneficial for biodegradable polymers, in which the processability window is very narrow. In this study, morphology, rheological, and mechanical properties of parts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Volpe et al [70] concluded that longer flow paths and faster cycle times can be obtained compared to usual injection molding due to the plasticization effect induced by the added supercritical blowing agent (i.e., the glass transition and melting temperature are decreased and the melt viscosity is reduced). Guanghong et al [135] reviewed microcellular foams having uniform cell diameters of 1 to 100 µm, and Xu et al [133] reviewed cell densities of 10 5 to 10 9 cells per cubic centimeter for foams produced by this technique.…”
Section: Foam Injection Moldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Volpe et al [70] concluded that longer flow paths and faster cycle times can be obtained compared to usual injection molding due to the plasticization effect induced by the added supercritical blowing agent (i.e., the glass transition and melting temperature are decreased and the melt viscosity is reduced). Guanghong et al [135] reviewed microcellular foams having uniform cell diameters of 1 to 100 µm, and Xu et al [133] reviewed cell densities of 10 5 to 10 9 cells per cubic centimeter for foams produced by this technique.…”
Section: Foam Injection Moldingmentioning
confidence: 99%
“…Different works have reported the use of SFCs as foaming agents for PLA. Nitrogen was used for injection molding [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] and batch foaming [ 72 ]. However, Li et al [ 73 ] showed that the solubility of CO 2 in PLA is approximately ten times that of N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Core-back foaming was realized to be an effective way to improve the cellular density of samples produced via FIM. [21][22][23][24][25][26][27] In the typical method of combining FIM with core-back technology, a movable mold is retracted for a short distance immediately or slightly after the gas-laden polymer melt is either fully or partially injected into the mold cavity, leading to the mold cavity being partially opened. There are generally two benefits to this operation: the core-back allows the foamed components more space and the pressure drop rate of the mold cavity increases, resulting in possible improvements in the foaming ratio and cellular density.…”
Section: Introductionmentioning
confidence: 99%
“…To save raw materials and provide sound absorption and shock resistance, polymer foaming has gradually become a common processing technology with a wide application range from industrial and agricultural production to the national defense industry [16][17][18][19][20]. PP is no exception and therefore has been the focus of research in recent years [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%